1996
DOI: 10.2307/1543023
|View full text |Cite
|
Sign up to set email alerts
|

Homeotic Transformation of Crab Walking Leg into Claw by Autotransplantation of Claw Tissue

Abstract: Homeotic transformation is defined as transformation of one body part into the likeness of something else. By autotransplantation of crab claw tissue into the autotomized stump of the fourth walking leg, the stump can regenerate a complete claw. Frozen claw tissue, sham operation, or walking leg tissue had no such activity. Contralateral autotransplantation of claw tissue into the autotomized stump of the fourth walking leg can induce the regeneration of a claw with normal handedness. Most of the transformed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The outgrowths in the present experiments lacked an articulation. Kao and Chang (1996) reported that dactyl, pollex, and ischium tissues of the claw of the crabs Cancer anthonyi Rathbun, C. gracilis Dana, and C. productus Randall have claw-transforming activity, based on autotransplantation of claw tissue into the autotomized stump of the walking leg. Cole (1910) pointed out that an extra claw did not develop from the middle of the outside face of the propodus, but did develop from the base of the propodus.…”
Section: Discussionmentioning
confidence: 99%
“…The outgrowths in the present experiments lacked an articulation. Kao and Chang (1996) reported that dactyl, pollex, and ischium tissues of the claw of the crabs Cancer anthonyi Rathbun, C. gracilis Dana, and C. productus Randall have claw-transforming activity, based on autotransplantation of claw tissue into the autotomized stump of the walking leg. Cole (1910) pointed out that an extra claw did not develop from the middle of the outside face of the propodus, but did develop from the base of the propodus.…”
Section: Discussionmentioning
confidence: 99%
“…Kao and Chang (1996) proved that dactyl, pollex, and ischium tissues of the crab claw all had claw-transforming activity if they were autotransplanted into the autotomized stump of the fourth walking leg. Furthermore, by autotransplantation of a pollex into the eye sockets, a claw with complete proximal segments (ischium, merus, carpus and manus) developed (Kao and Chang, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…There are many works that concern tissue transplantation experiments on various species: Xenopus laevis and Xenopus Borealis [1,2,3,5,7,9,10,11,12,13,14,16,17,18,19,21,22,25,26,31,34,35,36], chick [15,20,32,37], Hydra attenuata [29], Cancer gracilis and other crabs [23,24]. We consider a standard paradigm: one tissue that appears in normal development (donor tissue) is transplanted to another tissue (possibly with the removal of some tissues) that appears in normal development (host tissue), then observe what the grafted tissue will develop into (host tissue, donor tissue, or neither), and whether the development is normal or abnormal.…”
Section: Summary Of Transplantation Experimentsmentioning
confidence: 99%